Discovery of the Wall of Lima - San Cristóbal, Antonio (2003)
The discovery of a part of the Wall of Lima, between Abancay and Lampa avenues, next to the San Francisco convent, built by the government of the Virrey, Duque de laPalata, allows to expand the knowledge about how was the great virreinal wall of Lima, because it improves a new vision, not known so far by conventional historians.Because of this discovery it is necessary to rectify the route commonly offered by the maps of Lima like the projection of Nolasco in case of the bastions as well as the vertical projection refered to the existence of the great wall at the urban sector of the river cliff.